Guardrail evaluation for hazards on low-volume rural roads in Kansas - Wang, Peng (Kansas State University, 2020)
Rural crashes, specifically roadside crashes, account for a disproportionately high number of fatal vehicle crashes in the United States. In 2017, the fatality ratios of rural crashes in Kansas was higher than the national average. Therefore, the Kansas Department of Transportation (KDOT) is continuously seeking to prevent and reduce rural roadside crashes. This research project was funded by KDOT to study the benefit-cost ratios of implementing guardrails to shield bridges, culverts, and embankments on low-volume rural roads in Kansas to reduce vehicle crash fatalities and decrease rural transportation expenditures. This study utilized RSAPv3 simulation because it implements previous crash statistics and could be readily updated with local data. With the help of KDOT staff, the research team synthesized traffic operation data and geometric features on rural roads in Kansas and carried out crash simulations using RSAPv3 to determine if the benefits of guardrail implementation exceeded the corresponding costs. The results were intended to help local engineers decide whether to implement guardrails in roadside locations with hazards. Meanwhile, the simulation also revealed significant contributing factors to rural roadside crashes. Survey results and simulation outcomes showed similar patterns. Based on project results, the benefit-cost ratios did not justify the implementation of new guardrails for bare culverts or bare embankments on rural roads in Kansas. However, W-beam guardrails were efficiently implemented on bridges with medium-hazard-level edges without attaching bridge-approach guardrails. Likewise, for bridges with TL-2 bridge rails, study results did not justify implementing bridge-approach guardrails.
Keywords: Guardrail evaluation; Low-volume rural roads in Kansas; RSAPv3; Benefit cost analysis; Culvert, embankment, and bridge; Roadside crashes